IMPLEMENTASI MCCALL’S FRAMEWORK DALAM PENGUJIAN KUALITAS PERANGKAT LUNAK (STUDI KASUS PORTAL KULIAH KERJA NYATA UNIVERSITAS RIAU) - Yanti Andriyani; Justisia Amru Dewana; Ibnu Daqiqil Id (JURNAL TEKNIK INFORMATIKA, 2020)
Quality test is a crucial phase in the system development process to ensure that system work as its requirement. Therefore, the Portal Kukerta (Kuliah Kerja Nyata) Universitas Riau, an information system to manage data and activities of Kukerta, needs to assess. In this research, Portal Kukerta has been assessed using the McCalls software quality framework. The aspect that is focused on this research is product operation. Product operation consists of correctness, usability, integrity, reliability, and efficiency. The data collected by distributing questionnaires to 67 participants. The results show that users give a positive response to two aspects, namely  efficiency 99.90% and usability 64%. However, for the reliability factor 43%, correctness 48%, integrity 56% get a neutral value that there are aspects that are considered less by the user. Based on these results, it can be concluded that the Kukerta portal is very efficient in managing the data of Kukerta University of Riau and can be easily used by users. However, in terms of reliability, correction, and integrity need to be improved. The implication of the research are (1) providing a reference in assessing quality of a software and (2) specifically providing a recommendation for Portal Kukerta Universitas Riau for their system improvements.